Impact of psychotic symptoms on clinical outcomes in delirium - Paik, Soo-Hyun (PLoS One, 2018)
Delirium is an acute disturbance in attention and awareness in response to one or more physiological stressors that is closely related to poor clinical outcomes. The aim of this study is to investigate whether delirium patients with psychotic symptoms (PS) would have unique clinical characteristics and outcomes. A retrospective chart review was performed on the patients with delirium due to general medical conditions to assess clinical characteristics and outcomes. All patients were assessed by Delirium Rating Scale-revised-98 and classified as having PS when scored two or more on at least one of the psychotic symptom items (perceptual disturbances, delusions, and thought process abnormalities). Of 233 patients with delirium, 116 (49.8%) manifested PS. Patients with PS were younger, more likely to use antipsychotics to manage delirium, and had more hyperactive motor subtype than patients without PS. Logistic regression analysis showed that odds ratio of psychotic symptoms for having in-hospital mortality was 0.27 (95% CI = 0.08–0.94) after controlling age, sex, disease severity, comorbidity, number of medications, etiologies, motor subtypes, delirium severity and use of antipsychotics. The present study demonstrated that PS of delirium was associated with unique clinical characteristics and may affect the clinical course in a psychiatry-referral sample.